Reasoning Ecological Fatwas: The Progressive Response of the Indonesian Ulema Council (MUI) to the Phenomenon of Climate Change in Indonesia - Mufid, Moh. (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
This article aims to discuss the epistemological footing of MUI's ecological fatwa and its contribution in responding to the phenomenon of climate change. Today's environmental crisis is no longer a threat to the earth, but has become a reality. Climate change that occurs on a national and global scale leaves a negative impact on the lives of the earth's inhabitants. One of the causes of the environmental crisis is the attitude of humans who are not friendly to the environment. Humans as God's ambassadors on earth are arbitrary in utilizing the potential of natural resources destructively and exploitatively. Therefore, guidance is needed for Muslims in their interactions with the surrounding environment. MUI as a religious authority has contributed in overcoming the environmental crisis and climate change. The ecological fatwas issued by MUI are expected to be able to change the attitude and behavior of Muslims to become environmentally aware (eco-literacy). Epistemologically, MUI's environmentally friendly fatwas are based on maqāṣid sharī'ah reasoning through maslahat-mafsadat analysis. The approach used in finding the value of the spirit of environmental conservation is based on naṣ qaṭ'ī, qaulī and manhajī methods. These three sources of knowledge are formulated in an environmentally friendly fatwa product as a response to the environmental crisis that has become a global discourse today. Thus, MUI's fatwa can function as a tool of social control and a tool of social engineering at the same time.